Analysis of the Acceptance of the Local Tax Administration System Using the Technology Acceptance Model (TAM) - Antoro, Aji Fajar Suryo; Thaha, Abdurrahman Rahim (Ilomata International Journal of Tax and Accounting, 2025)
Local governments continuously strive to provide the best public services to their citizens, one of which is tax administration services through digital platforms. Each region faces unique challenges in developing an online system for local tax administration, making it crucial to understand the factors influencing the effectiveness of these services. This study uses the Technology Acceptance Model (TAM) as a conceptual framework and Partial Least Squares Structural Equation Modelling (PLS-SEM) using the Smart PLS application to analyze the factors affecting the acceptance of the Local Tax Administration System (SiPAD) by 131 taxpayers in Boyolali Regency. The results of hypothesis testing reveal that experience, compatibility, complexity, perceived ease of use, and perceived usefulness have varying impacts on the acceptance of SiPAD, with three hypotheses accepted and seven rejected. These findings underscore the importance of making SiPAD user-friendly, compatible, and perceived as useful to enhance the efficiency and effectiveness of tax administration and increase local tax revenue. The study also highlights the need for adequate training and socialization for taxpayers to keep pace with rapid technological developments. A well-implemented system is expected to expand the taxpayer base and support the success of local tax administration reforms.